2006
DOI: 10.1212/01.wnl.0000200779.03748.0f
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate in essential tremor

Abstract: Topiramate was effective in the treatment of moderate to severe essential tremor. Tremor reduction was accompanied by functional improvements, such as in motor tasks, writing, and speaking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(83 citation statements)
references
References 18 publications
2
77
0
4
Order By: Relevance
“…It has been studied in the largest study for ET so far [50]. Four relevant studies [50][51][52][53] assessed the effect of topiramate in limb tremor, providing evidence for therapeutic benefit [50][51][52][53].…”
Section: Topiramatementioning
confidence: 99%
See 2 more Smart Citations
“…It has been studied in the largest study for ET so far [50]. Four relevant studies [50][51][52][53] assessed the effect of topiramate in limb tremor, providing evidence for therapeutic benefit [50][51][52][53].…”
Section: Topiramatementioning
confidence: 99%
“…Four relevant studies [50][51][52][53] assessed the effect of topiramate in limb tremor, providing evidence for therapeutic benefit [50][51][52][53]. A placebo-controlled cross-over study in 24 patients using up to 400 mg/d as mono-or adjunct therapy [51] found a significant reduction of tremor subscores.…”
Section: Topiramatementioning
confidence: 99%
See 1 more Smart Citation
“…Severe cases cause substantial disability, especially in the elderly, and, if medications such as propranolol, primidone, and topiramate fail, patients may require surgical treatment with deep brain stimulation (2,3).…”
mentioning
confidence: 99%
“…Topiramate is effective in the treatment of moderate to severe essential tremor (Level B). Functional improvements accompany tremor reduction, such as in motor tasks, writing, and speaking [28]. The most common treatment-limiting adverse events in topiramate-treated patients are paresthesia, nausea, concentration/attention difficulty, and somnolence.…”
Section: Criteria For Possible Etmentioning
confidence: 99%